Efektivitas Simulasi Manajemen Bencana dalam Meningkatkan Kesiapsiagaan Tenaga Kesehatan: Systematic Review - Edi Purnomo; Zulhaini Sartika A. Pulungan; Muhammad Fathi Zihni Purnomo (Mando Care Jurnal, 2026)
Health workers are the front line of the health system, including in disaster crisis management. Improving preparedness through simulation activities is essential to minimize the risks and negative impacts caused by disasters. This systematic review aims to identify the effectiveness of simulations in improving the preparedness of health workers in dealing with disasters. Literature searches were conducted on six databases, namely Scopus, ProQuest, ScienceDirect, ClinicalKey Nursing, EBSCOHost, and PubMed. The inclusion criteria consist of a full-text article discussing disaster management simulations and disaster preparedness of health workers, published in English between 2013 and 2023. The initial search yielded 80,276 articles; after removing duplicates and filtering, 9 articles were selected for analysis, with an article quality score of 75 – 100%. Analysis of 9 articles shows that simulation methods are effectively used to increase the preparedness of health workers in handling disasters. In conclusion, simulation is a method that can be used to test the readiness of health workers in real-life disaster scenarios.